Peningkatan Pengetahuan Pimpinan Lembaga Kemasyarakatan Desa Mengenai Pengelolaan Dan Pengolahan Sampah Rumah Tangga - Azzahra Mubyaring Putri Sayekti; Ririt Iriani Sri Setiawati; Putra Perdana (CV. ITTC INDONESIA, 2022)
Managing and processing of household waste must be started by knowledge of the community. This community service is giving education to resident of village about how important of managing and processing of household waste for bring up clean and healty environment, introducing types of trash and explaining methods of managing trash with burying and recycling, and helping resident of Bandarasri village to doing manage and process of household waste. The target of this community service are leaders of society organization, expecting deployment of information and mover of managing and processing of household waste. Method of this community service is socialization with materials about types of trash, sorting household waste, managing organic household waste, and Reduce, Reuse, Recycle, Replace and Replant. The result of this community service shows good impact about increase in the number of society who understand about the materials.